Analysis Of The Relationship Between HBA1C and Serum Galectin-3 Levels in Subjects With Type 2 Of Diabetes Mellitus - Zaifah Firayanti; Yuyun Widaningsih; Liong Boy Kurniawan; Himawan Sanusi; Andi Alfian Zainuddin; Tenri Esa (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Type 2 diabetes mellitus is a disease characterized by increased blood glucose levels known as hyperglycemia. This disease can be diagnosed by examining HbA1c (glycated hemoglobin). Hemoglobin A1c is a minor component of hemoglobin related to glucose. Meanwhile, galectin-3 is a protein encoded in humans by the LGALS3 gene. This study aimed to clarify the relationship between HbA1c and serum galectin-3 levels in patients with type 2 diabetes. This study was conducted using an observational analysis technique with a cross-sectional study design. This research was conducted at the Clinical Pathology Laboratory, Hasanuddin University State University Hospital, and Laboratorium Universitas Hasanuddin Medical Research Center State College Hospital Universitas Hasanuddin Makassar. This research was conducted from January to March 2023. The population in this study were all patients with type 2 DM who visited the Hasanuddin University Hospital (RSPTN-UH) for treatment a total of 112 patients. Research sampling technique with non-probability purposive sampling. The sample of this study was 60 patients. Data analysis with the Independent T-test or Mann-Whitney test. The results of the study were that serum Galectin-3 levels in uncontrolled type 2 diabetes mellitus had a higher average value of 20.18 ± 6.15 ng/mL compared to controlled type 2 diabetes mellitus, namely 14.80 ± 6.41 ng/ mL although there was a statistically significant difference (p=0.012) but no significant correlation was found between HbA1c and serum Galectin-3 levels in type 2 diabetes mellitus subjects (r=0.176 p=0.179) with the distribution of data in the Scatterplot not forming a linear relationship pattern. It is recommended that type 2 Diabetes Mellitus patients carry out an HbA1c examination as an effective test to control glucose levels, reduce the risk of complications, and maintain a healthy lifestyle to avoid type 2 DM.Keyword: HbA1c, Serum Galectin-3, Type 2 Diabetes Mellitus